Image enhancement of photoacoustic imaging for early endometrial cancer detection by employing a filtered delay multiply and sum beamforming algorithm - Yongping Lin (AIP Advances, 2019)
In endometrial cancer, patients in early stages have a 91% 5-year survival chance. By contrast, patients in advanced stages have only 20% survival chance. Therefore, early diagnosis of endometrial cancer is very important. Photoacoustic imaging is able to distinguish benign from malignant tumors. However, the images acquired through photoacoustic imaging contain inherent artifacts, caused by imperfect reconstruction algorithms. In this paper, to improve the said images, a filtered delay-multiply-and-sum (F-DMAS) algorithm, which was proven to have an increased dynamic range and better quality of B-mode images was employed in the reconstruction process. First, the images of two blood vessel phantom experiments, acquired through photoacoustic imaging, were reconstructed by employing the F-DMAS algorithm. The results show the lateral resolutions of the system improving from 2.22 mm (with traditional photoacoustic imaging reconstruction algorithms) to 1.47 mm. Next, images of a pig uterus, filled with intralipid-20% emulsion, were also reconstructed by employing the F-DMAS algorithm. The average signal-to-noise ratio increased from 11.14 dB (with traditional photoacoustic imaging reconstruction algorithms) to 64.90 dB. In order to improve the continuity of the 3D PA image, F-DMAS with an adaptive coefficient was discussed to find the best balance between the signal-to-noise ratio and continuity. In conclusion, this paper demonstrates that the use of F-DMAS algorithms in the reconstruction of the images acquired through photoacoustic imaging in clinical investigations would improve the detection rate of early endometrial cancer.